2018
DOI: 10.1051/matecconf/201825006012
|View full text |Cite
|
Sign up to set email alerts
|

Microplastics in sediment from Skudai and Tebrau river, Malaysia: a preliminary study

Abstract: Plastic debris floating on surface water has now become an environmental issues concerning its abundance and fate. Generally, plastic debris that are fragmented into less than 5 mm in size is known as microplastics (MP). To date, discovery on the occurrence and impacts of MP in marine environments have been reported by many studies. However, less investigation has been carried out in freshwater environments. The occurrence of MP in Malaysia is also unknown. Thus, the present study has characterised the abundan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(15 citation statements)
references
References 29 publications
1
13
1
Order By: Relevance
“…Surface water of Surabaya River, Indonesia were dominated with film [49]. The same results were also obtained in Skudai and Tebrau Rivers, Malaysia [54], Pearl River, China [30] and Wei River, China [33].…”
Section: Morphological Characteristics and Sources Of Microplasticssupporting
confidence: 77%
“…Surface water of Surabaya River, Indonesia were dominated with film [49]. The same results were also obtained in Skudai and Tebrau Rivers, Malaysia [54], Pearl River, China [30] and Wei River, China [33].…”
Section: Morphological Characteristics and Sources Of Microplasticssupporting
confidence: 77%
“…For instance, a Google Scholar search conducted in January 2020 have only returned nine studies of microplastic pollution that have been published in Malaysia, of which two are related to freshwater systems. Of those on freshwater, one was a study of microplastic present in riverbed sediments [56] and the other an assessment of loads in a lake dwelling fish [57]. Thus, no published studies of loads carried by rivers, uptake by river organisms or risks to humans from contaminated potable water supplies or food derived from rivers (notably fish) have been conducted in Malaysia.…”
Section: Waste Recovery Processmentioning
confidence: 99%
“…As stated by Sarijan et al., [ 90 ] microplastic in the film shape is highly found in both Skudai and Tebrau River, Johor. Meanwhile, yellow, and white colors of microplastic were dominant in the Skudai River, and blue appears to be the dominant color found in Tebrau River.…”
Section: Heterogeneity On Abundance and Distribution Of Microplastic ...mentioning
confidence: 73%
“…Additionally, Sarijan et al. [ 90 ] have reported an abundance of microplastic between the Skudai and Tebrau Rivers. It is observed that the average concentrations of particles found in the Skudai and Tebrau Rivers were 0.20 and 0.68 particles m −3 , respectively that were dominated by size ranging from 1000 to 5000 µm.…”
Section: Heterogeneity On Abundance and Distribution Of Microplastic ...mentioning
confidence: 99%